UJI DIAMETER PULI PADA ALAT PENGEMPA MINYAK KEMIRI ( Pulley Diameter Test Of Candlenut Oil Press ) - Taufik Jamaluddin Sitepu; Ainun Rohanah; Achwil Putra Munir (Universitas Sumatera Utara, 2017)
ABSTRACT In the oil press equipment (screw type) diameter of pulley must be considered. The diameter determines the outcome of the candlenut oil. This study was the effect of severed rotation of the screw type press oil on the yield and quality of candlenut oil. The study was conducted at the Laboratory of Agricultural Engineering and analysis was done at Analysis Laboratory of Food Chemistry, Faculty of Agriculture USU in December 2014 until march 2015 using a non factorial completely randomized design with three levels of pulley diameter ( 3 cm, 4cm, dan 5cm ). Parameters measured were effective equipment capacity water content, and yield. The results showed that the diameter had highly significant effect on the capacity of effective equipment moisture content and yield. The best treatment of this research was the treatment of P2 (0.290 1 / h) which produced water content of 0.95%, oil of 0.225 L / kg. Keywords: Pulley, oil press, candlenut. ABSTRAK Pada ala toil press tipe ulir pengaturan diameter pengempaan perlu diperhatikan. Diameter tersebut menentukan putaran hasi minyak kemiri. Penelitian ini adalah pengujian berbagai tingkat putaran pada alat oil press tipe ulir terhadap rendemen dan mutu minyak kemiri. Penelitiandilakukan di LaboratoriumKeteknikanPertaniandananalisis data di LaboratoriumAnalisis Kimia Bahan Pangan FakultasPertanian USU pada bulan Desember 2014 hingga Maret 2015 dengan menggunakan model rancangan acak lengkap non faktorial yaitu pada taraf pengujian pada pulley 3 cm, 4 cm dan 5 cm. Parameter yang diamati adalah kapasitas efektif alat kadar air, dan rendemen. Hasil penelitian menunjukkan bahwa uji diameter memberikan pengaruh berbeda sangat nyata terhadap kapasitas efektif alat kadar air, dan rendemen. Perlakuan terbaik dari penelitian ini adalah perlakuan P2 (0,290 1/jam ) yang menghasilkan kadar air 0,95%, dan rendemen murni 0,225 L/kg. Kata kunci: Pulley, alat pengempah minyak, kemiri